2020
DOI: 10.3389/fonc.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

BAG2 Promotes Proliferation and Metastasis of Gastric Cancer via ERK1/2 Signaling and Partially Regulated by miR186

Abstract: Bcl2-associated athanogene (BAG)2 as a co-chaperone has been demonstrated to be involved in tumor growth and metastasis, but its biological function in gastric cancer remains unknown. Here, we reported that BAG2 was highly expressed in gastric cancer cell lines and tissues, indicating poor prognosis. High expression of BAG2 was significantly associated with T stage and differentiation level of gastric cancer (P < 0.001). Functional experiments revealed that BAG2 knockdown in gastric cancer cells inhibited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…Among its targets, one of the most important is the heat shock protein 70 (Hsp70) [ 36 ]. In agreement with our study, BAG2 is frequently found to be upregulated in tumors, pointing out its ability to also promote proliferation and metastasis by promoting the accumulation of mutant p53 [ 37 , 38 , 39 , 40 ]. According to the results of our work and the knowledge on BAG2, studies evaluating strategies targeting BAG2 in the fight against MPM should be undertaken.…”
Section: Discussionsupporting
confidence: 92%
“…Among its targets, one of the most important is the heat shock protein 70 (Hsp70) [ 36 ]. In agreement with our study, BAG2 is frequently found to be upregulated in tumors, pointing out its ability to also promote proliferation and metastasis by promoting the accumulation of mutant p53 [ 37 , 38 , 39 , 40 ]. According to the results of our work and the knowledge on BAG2, studies evaluating strategies targeting BAG2 in the fight against MPM should be undertaken.…”
Section: Discussionsupporting
confidence: 92%
“…BAG2 signaling was predicted to be active after AUY-VE, although its protein level was decreased, according to the proteome analysis. BAG2 interacts with HSP70 to regulate its functions and suppresses apoptosis induction via BCL2 protein interactions [ 61 , 62 ]. Thus, reduced BAG2 and high HSP70 levels might contribute to CMA and apoptosis induction in A673 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IGF2BP3 has been found to be associated with chemotherapy resistance and poor prognosis of ovarian cancer (31)(32)(33). BAG2 can promote the metastasis and proliferation of gastric cancer (34). By affecting the MAPK/JNK signal pathway (35), RNF213 can inhibit the carcinogenesis of glioblastoma.…”
Section: Discussionmentioning
confidence: 99%